Los The political origins of democracy: Colonial legacy, war and political pacts in the construction of the Republic of Uruguay - Garcé, Adolfo (Revista de Historia, 2018)
It is well known that Uruguayan democracy is one of the most stable in Latin America. In contrast, the previous complex process prior to its establishment is less known outside Uruguay. Between 1830, when the first constitution was sworn, and 1917, when the second one was approved, the Uruguayan political process was characterized by its high degree of violence and conflict. Although it may seem contradictory, it is precisely in this long period of political failures that we must seek the keys of further success. Democracy was born out of an extensive sequence of frustrated attempts of exclusion followed by political deals. In turn, the attempts of exclusion executed by the successive governments failed because the State structures inherited from the colony were manifestly weak. Colonial legacy, frustrated hegemonic attempts (throughout the second half of the 19th century), and interparty negotiations (consummated at the beginning of the 20th century) make up the causal chain that explains, ultimately, the comparatively successful establishment of democracy in Uruguay.